KONDISI SOSIAL EKONOMI PARA PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) PADA MASA PANDEMI COVID-19 DI KEL. HELVETIA TIMUR - Khairunisa, Shania; Suriadi, Agus (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
Based on the results of the research conducted, even though the Covid pandemic condition which caused a decrease in the income of Micro, Small and Medium Enterprises players, they were still able to survive and were still sufficient to meet their needs. The education of the children of UMKM actors is fulfilled up to the informal sector. Adequate living conditions because it is already a permanent home. All MSME actors and their family members are registered in the BPJS program, as well as their employees are registered in the BPJS manpower program. Social interactions with family are harmonious, as well as with fellow business actors. Apart from the ability of MSMEs to maintain their economy during the COVID-19 pandemic, the authors suggest that the government be able to provide assistance that can be distributed evenly so that new and old MSMEs can compete in the future